(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Blue carbon is carbon absorbed and stored as biomass in coastal ecosystems. Seagrass meadows have the primary function of storing carbon. This study aims to determine the percentage of organic carbon content in the biomass and in the seagrass sediments, as well as total carbon stock in part of the National Marine Reserve Karimunjawa.The density and coverage of seagrass were made by means of quadrat transect and carbon content analysis was performed using Loss on Ignition (LoI) method. The highest average of organic carbon content percentage on belowground biomass was 33.13%, whereas from the aboveground biomass was 29.19% and in the sediment were 2.75% and 2.82% at Nyamuk Island (Station 1). Belowground biomass has higher carbon content than the aboveground, except for genus Halophila. Percentage of carbon weight in the sediment proved to be the highest contribution to the total carbon stock in seagrass meadows, i.e., 97.92-98.49%. The highest carbon weight was also established in Nyamuk Island, i.e.,13248.29 tons C/ha. Whereas, Pokemon beach in Kemujan Island (Station 2) fixing the highest carbon stock, i.e., 83003.14 tons C in its 7.68 ha seagrass area.